Antiinflammatory Activity of Some Substituted Naphthalenes - Deo, Sujata; Inam, Farhin; Mahashabde, R.P.; Jadhav, A.N. (Asian Journal of Chemistry, 2010)
1-Phenyl naphthoic acid, their methyl esters and pericarbonyl lactone systems were evaluated for their antiinflammatory potential. The lactones among the above, were found to be most active in the carrageenen paw edema test.